Nivolumab-induced diabetes mellitus—a case report with literature review of the treatment options - Daetwyler, Eveline; Zippelius, Alfred; Danioth, Simona; Donath, Marc Y.; Gut, Lara (Frontiers in Immunology, 2023)
Background: Immune checkpoint inhibitor (ICI) treatment has become important for treating various cancer types, including metastatic renal cell carcinoma. However, ICI treatment can lead to endocrine immune-related adverse events (irAEs) by overstimulating the patient's immune system.Here, we report a rare case of a new-onset of diabetes mellitus (DM), caused by nivolumab, and we discuss the feasible treatment options with focus on TNF-antagonism.Case presentation: A 50-year-old man was diagnosed with metastatic renal cell carcinoma. Due to systemic progression, a combined immunotherapy with ipilimumab and nivolumab was initiated, according to the current study protocol (SAKK 07/17). The administration of ipilimumab was stopped after 10 months, due to partial response as seen in the computer tomography (CT), and nivolumab was continued as monotherapy. 14 months after the start of the treatment, the patient was admitted to the emergency department with lethargy, vomiting, blurred vision, polydipsia and polyuria. The diagnosis of DM with diabetic ketoacidosis was established, although auto-antibodies to β-cells were not detectable. Intravenous fluids and insulin perfusor treatment were immediately initiated with switching to a subcutaneous administration after one day. In addition, the patient received an infusion of the TNF inhibitor infliximab four days and two weeks after the initial diagnosis of DM. However, the C-peptide values remained low, indicating a sustained insulin deficiency, and the patient remained on basal-bolus insulin treatment. Two months later, nivolumab treatment was re-started without destabilization of the diabetic situation.In contrast to the treatment of other irAEs, the administration of corticosteroids is not recommended in ICI-induced DM. Options for further treatment are mainly based on low numbers of case series and case reports. In our case, the administration of infliximabin an attempt to salvage the function of the -cellswas not successful, this in contrast to some previous reports. This apparent discrepancy may be explained by the absence of insulin resistance in our case. There is so far no evidence for immunosuppressive treatment in this situation. Prompt recognition and immediate start of insulin treatment are most important in its management.